Evaluation of Diagnostic Potential of Anti-Peptide Antibodies for Dengue Virus Infection - J. Jaya Supa Sooriya; J. Asnet Mary (International Journal of Pharma and Bio Sciences, 2020)
Dengue virus is diagnosed by antibodies, viral antigen, and nucleic acids. Serological techniques detect only at late acute phase that delay the appropriate treatment. Viral detection methods are expensive and required skilled professionals. Therefore, a rapid and accurate dengue diagnosis with cost effective is of paramount importance for effective control of dengue outbreaks. As antibodies of synthetic peptides reported in our previous work showed the potential binding between Dengue virus and antibodies, the present study aims to use anti-peptide antibodies for the purpose of diagnosis. The objective of the present study is to evaluate anti-peptide antibodies generated for three synthetic peptides of envelope glycoprotein for their diagnostic potential against dengue virus. Indirect ELISA was performed for detecting the antigen. A total of 80 serum samples from dengue infected and non-infected patients were evaluated using three anti-peptide antibodies raised against three synthetic peptides of envelope glycoprotein of dengue virus. Anti-peptide antibodies showed high sensitivity of 91%, 82%, and 90% against viral antigen for anti-peptide1 antibody, anti-peptide2 antibody and anti-peptide3 antibody respectively. The specificity of the anti-peptide antibodies was also found to be high in anti-peptide2 antibody and anti-peptide3 antibody. These anti-peptide antibodies detect the viral antigen by serological method. Therefore, the anti-peptide antibody based diagnosis can be a dependable alternative approach for the early diagnosis of the disease. This is the first article reporting anti-peptide antibodies generated against synthetic peptides of envelope glycoprotein of dengue virus for the serological diagnosis of dengue fever.